PEMODELAN DAMPAK BENCANA TSUNAMI KOTA PARIAMAN PROVINSI SUMATERA BARAT - SY, Arief Hamzi; Purwaningsih, Endah (DEPARTEMEN GEOGRAFI FIS UNP, 2026)
This study is about modeling the impact of the tsunami disaster which aims to, 1) Determine the area that has the potential to be affected by a tsunami at 5 meters, 10 meters and 15 meters of sea level rise. 2) Knowing the potential of buildings affected by the tsunami disaster. 3) Knowing the extent of damage to the agricultural sector affected by the tsunami at sea level rise of 5 meters, 10 meters and 15 meters in the agricultural sector. 4) Knowing the total value of physical losses and economic losses affected by the tsunami disaster. The type of research conducted is descriptive quantitative research. The modeling used is 3 heights of sea level rise on the coastline using the Cost-Distance analysis method, to determine the area affected by the tsunami disaster. And scoring to determine physical losses and economic losses based on the area affected by the tsunami. The indicators calculated are the area of ​​the affected area, the number of buildings affected, the area of ​​agriculture affected and the losses affected by the tsunami. The results of each modeling are different where the modeling of a 5 meter increase in water area affected is 1.057,63 Ha, the number of buildings affected is 7.280 units, the agricultural area affected is 221,38 Ha and for a loss of IDR 103.472.000.000,00. The increase in water is 10 meters, the area affected is 3.911,57 Ha, the number of buildings affected is 14.314 units, the agricultural area affected is 1.931,57 Ha and the loss is IDR 422.859.000,00. The increase in water is 15 meters, the area affected is 5.269,18 Ha, the number of buildings affected is 18.372 units, the agricultural area affected is 3.088,57 Ha and for a loss of IDR 671.345.000.000,00.